TINJAUAN YURIDIS STATUS KEWARGANEGARAAN INDIVIDU TERHADAP KELUARGA SIMPATISAN ISLAMIC STATE OF IRAQ AND SYRIA YANG BERADA DI WILAYAH KONFLIK BERDASARKAN HAK ASASI MANUSIA INTERNASIONAL - Desi Natalia Sihombing; Evi Deliana; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A person's citizenship status is so important, the international community makes several legal instruments that related to citizenship status. As stipulated inthe Universal Declaration of Human Rights 1948, International Convention on Civil and Political Rights 1966, Convention on the Rights of the child 1989, International Convention on the Elimination of All Forms of Discrimination Against Women 1979, International Convention relating to the Status of Stateless Person 1954 and International Convention on Reduction of Statelessness 1961. The right to renounce nationality was based on the principle that a person has the right to exercise his nationality, the reasonable requirements of the laws by involved of the country. This research will be structured by using the type of normative juridical research, that research was focused on examining the application of rules or norms in law to legal principles and theories which is carried out by conducting prior identification of a state policy on the citizenship status of ISIS sympathizer families. The data collection technique was used in this research is literature study. The approach used in this research is to use a normative approach, that namely library law research. In the results there are two main points that can be concluded. First, the rights of citizens who are reaffirmed, must be properly defended by the state or maintained by citizens, organized in countries regarding the citizenship status of ISIS sympathizer families. Two, based on positive law in Indonesia, there is no concrete accumulation that states that families of ISIS sympathizers are eligible to have their citizenship revoked.Keywords: Citizenship - ISIS - Policy - International of human rights